1999
DOI: 10.1038/sj.onc.1203001
|View full text |Cite
|
Sign up to set email alerts
|

Bax membrane insertion during Fas(CD95)-induced apoptosis precedes cytochrome c release and is inhibited by Bcl-2

Abstract: Ligation of the Fas cell surface receptor leads to activation of caspases and subsequent apoptosis. Members of the Bcl-2 family of proteins control the cellular commitment to apoptosis, although their role in Fasinduced apoptosis is ill-de®ned. In this report we demonstrate that the pro-apoptotic protein, Bax, translocates from the cytosol speci®cally to the mitochondria following Fas ligation in MCF10A1 breast epithelial cells. Bax translocation was dependent on caspase activation, and preceded the release of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
55
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(63 citation statements)
references
References 48 publications
8
55
0
Order By: Relevance
“…For example, in the nanodisc cryo-EM study, Volkmann et al 78 found that BCL-XL abolished the integration of BAX into nanodisc membranes in the presence of BID BH3 peptides. This agrees with other work 10,34,95,[110][111][112] showing that BCL-XL or BCL-2 can block membrane recruitment and integration of BAX, even in the presence of a BAX-activating signal. In other studies, membrane integration of both BCL-XL and BAX (i.e.…”
Section: How Does Bcl-xl Protect Against Cell Death?supporting
confidence: 81%
“…For example, in the nanodisc cryo-EM study, Volkmann et al 78 found that BCL-XL abolished the integration of BAX into nanodisc membranes in the presence of BID BH3 peptides. This agrees with other work 10,34,95,[110][111][112] showing that BCL-XL or BCL-2 can block membrane recruitment and integration of BAX, even in the presence of a BAX-activating signal. In other studies, membrane integration of both BCL-XL and BAX (i.e.…”
Section: How Does Bcl-xl Protect Against Cell Death?supporting
confidence: 81%
“…38 Consistent with a previous report, we have demonstrated that STP-induced Bax redistribution is independent of caspase activity. 32 However, Bax membrane translocation induced by Fas activation was caspase dependent, 39 indicating a differential requirement of caspase activity for this process depending on the apoptotic stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of caspase-8 could cleave its substrate Bid to generate 15 kD truncated Bid (tBid), which could be translocated to mitochondria to induce the release of cytochrome c thereby activating mitochondrial pathway of apoptosis [22]. Moreover, activation of caspase cascade might be correlated with migration of cytosolic Bax to the mitochondria where it could assist tBid in releasing cytochrome c into the cytosol [23]. We found that treatment with 4-HPR and IFN-γ caused significant increases in proteolytic cleavage of Bid to tBid in all glioblastoma cell lines (Fig.…”
Section: Activation Of Caspase-8 and Proteolytic Cleavage Of Bidmentioning
confidence: 99%